EVALUATION OF RENAL FUNCTION BEFORE AND AFTER CHEMOTHERAPY IN NASOPHARYNGEAL CARCINOMA IN LOMBOK - Hamsu Kadriyan; Muhammad Alfian Sulaksana; Nurhidayati; Baiq Endang Suprihartini (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2019)
Abstract Introduction: Combination of chemotherapy and radiation are the treatment of choice in advance stage of nasopharyngeal carcinoma. Cisplatin-based chemotherapy is a regiment of choice in those cases. Several studies show that cisplatin-based chemotherapy affect renal function. Objective: To evaluate and compare the renal function before and after chemotherapy through comparing the blood urea nitrogen and creatinine serum level in patients with nasopharyngeal cancer who receive cisplatin and paclitaxel chemotherapy. Method: Using Medical records data for study design. Design of this study is before and after using medical records data in West Nusa Tenggara General Hospital in Lombok. Result: There were 33 patients who fulfill the inclusion and exclusion criteria in this study. Most of the patients are male with male and female ratio 3:1. The youngest patient age is eight years old, on the other hand, the oldest is 70 years old with the average age 46.6 years old. According to histopathology finding, on this study researcher didn't found WHO type I and most the patients were WHO type III (89.9 %). The mean blood urea nitrogen concentration before chemotherapy is 25.00 and after the treatment 33.33 with the p-value 0.01 with the paired t-test. On the other hand, creatinine serum level before and after chemotherapy consecutively 0.99 and 1.10. P value 0.15, or there is no significant difference. Conclusion: Blood urea nitrogen and creatinine serum are increase after cisplatin-based chemotherapy. However, only BUN has a significant difference.